Preparation and characterization of apatite/cathode interfaces of solid oxide fuel cells - Heah, Min An. (2009)
The La9.5Si6O26.25 apatite type electrolyte was tested out with pure LSCF and LSM cathodes. It was benchmarked with other commonly used electrolytes such as GDC for intermediate temperature solid oxide fuel cells (IT-SOFCs) and YSZ for high temperature SOFCs (HT-SOFCs). XRD results of YSZ, LSM and NiO calcined with La9.5Si6O26.25 showed no presence of new phases at all selected temperatures. On the other hand, XRD results of GDC, LSCF and SSC calcined with La9.5Si6O26.25 have peak variations in their diffractograms as temperature was raised. EIS tests under the temperature range of 700°C to 900°C and oxygen partial pressures of 0.01 – 1 atm were done for both LSM and LSCF cathodes. At 0.21 atm and 900°C, LSCF and LSM cathode impedance values were 0.272 Ωcm2 and 5.169 Ωcm2 respectively when used with the apatite electrolyte. These results were higher than the benchmarks.